Structural and mechanistic studies on 2-oxoglutarate-dependent oxygenases and related enzymes. - Schofield, C; Zhang, Z (1999)
Mononuclear nonheme-Fe(II)-dependent oxygenases comprise an extended family of oxidising enzymes, of which the 2-oxoglutarate-dependent oxygenases and related enzymes are the largest known subgroup. Recent crystallographic and mechanistic studies have helped to define the overall fold of the 2-oxoglutarate-dependent enzymes and have led to the identification of coordination chemistry closely related to that of other nonheme-Fe(II)-dependent oxygenases, suggesting related mechanisms for dioxygen activation that involve iron-mediated electron transfer.